MENGATASI KEMISKINAN: AGENDA PEMBANGUNAN YANG TAK PERNAH SELESAI* - Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1996)
Development for three decades in Indonesia has gained a significant result in lowering poverty. However, the statistic shows that a large number of people is still under poverty line. Inaddition, poverty has another dimension which might be more crucial to be solved, that are social and political poverty. The next unfinished agenda of development is how to solve this problem to accelerate the success of economic poverty aleviation.